Immanuel Kant : autonomia e pedagogia - Vaz, Alexandro do Nascimento (2011)
This research goal to investigate the relationship between autonomy and teaching-learning process, from the pedagogical reflections by of Immanuel Kant. This relation refers to the moral and ethical conceptions of that author. The research goal is to establish a reciprocal relationship between a process of teaching and learning, from birth to adulthood, the concept of autonomy and the implication that this formative idea of the century XVII is at the same time. There are three orienting questions: What is the concept of autonomy proposed by Kant? What is the proposal for education proposed by Kant? What is the objective formative Kantian? The research was conducted bibliographic and analytically reconstructed the works Fundamental Principles of the Metaphysic of Morals, On pedagogy, post-critical texts and works of commentators. There were three axis that organized the research. First, we addressed the question of autonomy and we make to reference to ethical reflection and moral, expressed by Kant in his work Fundamental Principles of the Metaphysic of Morals, defining what is meant by autonomy. The second axis, we approach the problem of education (pedagogic) itself, evaluating the formation of the subject from birth to adulthood and having as reference in this research the work On pedagogy. Inside this context put into question the pedagogical methods and the peculiarities inherent in the Kantian educational process, relating them to the concept of autonomy. Finally, we investigate how this process of teaching and learning focuses on the subject and what the concept of human formation proposed by Kant, based on post-critical Kantian texts